Two essays on innovation and growth in China - HE, Qiugu (Institutional Knowledge at Singapore Management University, 2021)
This dissertation studies China’s economic growth from a perspective of industry dynamics. In chapter 1, I introduce the background and policies relating to China’s economic growth after 1978. In chapter 2, I find that the elasticity of the average R&D expenditure of firms on competition is -0.29 in weak-IPR (intellectual property right) provinces, and -0.06 in strict-IPR provinces. Next, I use the Schumpeterian growth model to explain this finding: When the market becomes more competitive, a firm prefers imitation to innovation to a larger extent, as a means of getting new technology. Due to enforcement of IPR laws, the imitation replaces innovation more slowly in strict-IPR provinces, compared to weakIPR provinces. In chapter 3, I estimate the TFPs of exporting and importing varieties for 6827 firms from 2002 to 2007 in the garment industry. I present three main channels of the growth of the aggregate TFPR(revenue) of continuous exporters: technology upgrade, reallocation of resources within continuous-exporting products, and switch of products. These three channels explain 27.2%,15.3%, and 9.46% of the aggregate TFPR growth, respectively. From the import side, the adjustment of import counts by firms explains 0.1% of the aggregate TFPR growth.